Pengembangan E-Modul Materi Sifat-Sifat Cahaya Berbasis Discovery Learning untuk Siswa Kelas IV SDN Bumiayu 2 Kota Malang - Alma Kumala Dani; Sukamti Sukamti; Sri Estu Winahyu (Universitas Negeri Malang, 2022)
Abstract: Researchers conducted development research aimed at producing discovery learning-based e-module teaching materials for the fourth grade elementary school students that are practical and interesting when used in learning and produce products that are suitable for use based on the assessments of material experts, media experts, and teachers. as a user. Researchers found problems, namely the lack of development of teaching materials when learning online and offline, and information obtained that most teachers only rely on teaching materials published by the government and LKS from schools, not all available teaching materials contain detailed learning materials, especially on science content. the properties of light in grade IV elementary school. The method used in this research is RnD with ADDIE model.The results of the product validity test are very valid and can be tested without revision by media experts with a percentage of 96, 36 percent, material experts 98, 75 percent, and users of 88, 18 percent. In addition, this teaching material product was tested in a small stage with the number of students 6 students and a large test stage of 24 fourth grade elementary school students. The results of the trial get a practical response value from students with an average percentage of 96, 63 percent. According to the calculation of the assessment results, the e-module teaching material product deserves to be tested without revision. Abstrak: Peneliti melakukan penelitian pengembangan bertujuan menghasilkan produk bahan ajar e-modul materi sifat-sifat cahaya berbasis discovery learning untuk siswa kelas IV sekolah dasar yang praktis dan menarik ketika digunakan dalam pembelajaran serta menghasilkan produk yang layak digunakan berdasarkan penilaian ahli materi, ahli media, dan guru sebagai pengguna. Peneliti menemukan permasalahan yaitu kurangnya pengembangan bahan ajar ketika pembelajaran online maupun offline, serta diperoleh informasi bahwa kebanyakan guru hanya mengandalkan bahan ajar yang diterbitkan oleh pemerintah dan LKS yang dari sekolah, tidak semua bahan ajar yang tersedia memuat secara rinci materi pembelajaran terutama pada muatan IPA materi sifat-sifat cahaya pada kelas IV sekolah dasar. Metode yang digunakan dalam penelitian ini adalah RnD dengan model ADDIE. Hasil uji kevalidan produk masuk kriteria sangat valid dan dapat diuji coba tanpa revisi oleh ahli media dengan persentase 96, 36 persen, ahli materi 98, 75 persen, dan pengguna sebesar 88, 18 persen. Selain itu, produk bahan ajar ini diujicobakan dalam tahap kecil dengan jumlah siswa 6 siswa dan tahap uji besar 24 siswa kelas IV sekolah dasar. Hasil ujicoba mendapatkan nilai respon kepraktisan dari siswa dengan rata-rata persentase sebesar 96, 63 persen. Menurut perhitungan hasil penilaian, produk bahan ajar e-modul layak diuji coba tanpa revisi.